High Performance Liquid Chromatographic Method for Determination of Ascorbic Acid in Pure Form, Pharmaceutical Formulations, Biological Samples and in Environmental Water Samples - Nief Rahman Ahmed; karam Basil (College of Pharmacy / Mustansiriyah University, 2014)
A simple, precise, rapid, and accurate reversed-phase high performance liquid chromatographic method has been developed for the determination of ascorbic acid in pure from, pharmaceutical formulations, biological samples and in environmental water samples. Chromatography was carried out on supercar L1 (C18 ) reversed- phase column (25cm× 4.6mm), 5 microns, using a mixture of methanol : water (42: 58v/v) as a mobile phase at a flow rate of 1.0 ml.min-1.Detection was performed at 254nm at ambient temperature. The retention time for ascorbic acid was found 2.3 minutes. The calibration curve was linear (r= 0.9998) over a concentration range from 0.5 to 12.5μg/ml. Limit of detection (LOD) and limit of quantitation (LOQ) were found 3ng/ml and 9 ng/ml respectively. The method was validated for its linearity, precision and accuracy. The proposed method was successfully applied for the determination of ascorbic acid in pure form, pharmaceutical formulations, and biological samples and in environmental water samples.